2012
DOI: 10.2308/accr-50156
|View full text |Cite
|
Sign up to set email alerts
|

Identity, Incentives, and the Value of Information

Abstract: We examine the impact of identity preferences on the interrelation between incentives and performance measurement. In our model, a manager identifies with an organization and loses utility to the extent that his actions conflict with effort-standards issued by the principal. Contrary to prior arguments in the literature, we find conditions under which a manager who identifies strongly with the organization receives stronger incentives and faces more performance evaluation reports than a manager who does not id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Similar to psychological costs from deviating from norms (Akerlof & Kranton , ; Heinle et al, ), accountability can be interpreted as a psychological cost imposed on the agent . It is a cost that goes beyond possible monetary costs of justification by documenting available project options.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to psychological costs from deviating from norms (Akerlof & Kranton , ; Heinle et al, ), accountability can be interpreted as a psychological cost imposed on the agent . It is a cost that goes beyond possible monetary costs of justification by documenting available project options.…”
Section: The Modelmentioning
confidence: 99%
“…5 Intuitively, investors' expectations of a firm's performance are to some extent exogenous; or, the firm's profit target breaks down to targets for individual divisions and employees so that the threshold is exogenous to the contractual relation between employee and immediate superior. 6 Similar to psychological costs from deviating from norms (Akerlof & Kranton 2000Heinle et al, 2012), accountability can be interpreted as a psychological cost imposed on the agent. 7 It is a cost that goes beyond possible monetary costs of justification by documenting available project options.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Akerlof and Kranton (2005) show that employees identifying with the …rm accept lower wages and require lower incentives. The authors consequently claim that it is valuable for …rms to invest in changing their employees'identity (also see Heinle et al 2012, who derive optimal contracts when agents may identify with the …rm in a multi-task setting). Carlin and Gervais (2009) model morality as a self-imposed restriction to exert high e¤ort.…”
Section: Related Literaturementioning
confidence: 99%
“…Also, the authors observed that CEO organization identification is a substitute for external controls mechanisms with respect to agency problems, therefore reducing the overall agency costs. Finally, Heinle, Hofmann and Kunz (2012) presented theoretical arguments suggesting that firms which successfully implemented identity initiatives can undermine managers' effort in short-term and boost long-term value generation.…”
Section: A Principal-agent Model For Family Firmsmentioning
confidence: 99%